Linking Community and Pedagogy: Ethnomodels from Coastal Villages in Panay, Philippines - Renato V. Herrera Jr.; Emellie G. Palomo (Philippine Social Science Journal, 2022)
This design ethnography was conducted in two fishing villages on Panay Island, Philippines. The study aimed to gather data about the mathematical activities of the fisherfolks to identify ethnomodels for the integration of learners' local mathematical knowledge into mathematics instruction. The local mathematical knowledge of the fisherfolks was used as inspiration and grounding for designing and developing a context-based teaching-learning material. Seven key informants were chosen purposively. Participant observation, ethnographic interviews, and elicitation techniques were used for data gathering and triangulation. Furthermore, IDEO's design thinking toolkit for human-centered design was used as a guide for designing and developing the teaching-learning material. The three-part analyses using LeCompte's item, pattern, and structure level analysis revealed that mathematical ideas were embedded in the activities of the fisherfolks and their cultural artifacts. Their mathematical ideas were elaborated in four ethnomodels integrated into the context-based activity book: "The Mathematics of the Fisherfolks".